Penggunaan Metode Resitasi Dalam Meningkatkan Hasil Belajar Siswa Madrasah Ibtidaiyah (MI) Bina Insani Kec. Gunung Labuhan Kab. Way Kanan Tahun 2019/2020 - Miming Arjuni; Duwi Masitoh (Tadzkirah : Jurnal Pendidikan Dasar, 2021)
ABSTRACT Based on the results of the researcher's pre-survey, in the results of the daily test results for the Islamic Education Subject for the 2019/2020 Academic Year, there were some students who had not yet completed it because the online learning process was not fully understood by students. Based on this, the formulation of the problem in this study is: "The application of the recitation method can improve student learning outcomes at Madrasah Ibtidaiyah (MI) Bina Insani Kec. Gunung Labuhan Kab. Way Kanan in 2019/2020? " The purpose of this study was to determine the application of the recitation method can improve student learning outcomes at Madrasah Ibtidaiyah (MI) Bina Insani Kec. Gunung Labuhan Kab. Way Kanan 2019/2020. The data collection technique used in this research is to use learning outcome tests, observation, and documentation. Based on the results of classroom action research and the discussion that has been stated, the following conclusions can be drawn: Learning using the Recitation Method can improve learning outcomes at Madrasah Ibtidaiyah (MI) Bina Insani Kec. Gunung Labuhan Kab. Way Kanan, it can be seen from the increase in the completeness of student learning outcomes in the first cycle of 68.80% and in the second cycle is 89.76%. This means that there is an increase from cycle I to cycle II of 20.96%